PERGURUAN TINGGI ISLAM DI ASIA TENGGARA DI TENGAH TANTANGAN GLOBAL : SEBAGAI ACUAN ISTAC - Ali Murtopo (El-Idare, 2016)
The study of civilization is getting the attention of the world's universities. Both were developed in the form of study centers of civilization, the center of dialogue between civilizations, research, seminars and workshops, or scientific journals. Issues of culture, civilization and national identity and culture community clumps, like the Malay Archipelago, a major theme in the discourse of post-colonial (post-colonial) and globalization. As a reference to develop in ways that empower, should look at the senior colleges existing in Southeast Asia, for example ISTAC.